The making of an embryo in a basal metazoan: Proteomic analysis in the sea anemone Nematostella vectensis. Issue 23 (9th November 2015) - Levitan, Shimrit; Sher, Noa; Brekhman, Vera; Ziv, Tamar; Lubzens, Esther; Lotan, Tamar
Abstract : Cnidarians are widely distributed basal metazoans that play an important role in the marine ecosystem. Their genetic diversity and dispersal depends on successful oogenesis, fertilization and embryogenesis. To understand the processes that lead to successful embryogenesis in these basal organisms, we conducted comparative proteomics on the model sea anemone Nematostella vectensis . We examined four developmental stages from oocyte maturation through early embryogenesis, as well as the oocyte jelly sac in which fertilization and embryogenesis take place. Our analysis revealed 37 stage‐specifically expressed proteins, including cell cycle, cellular energy related and DNA replication proteins and transcription regulators. Using in situ hybridization, we show that within the mesenteria, two cell types support successful oocyte development and embryogenesis. Large somatic supporting cells synthesize vitellogenin, the most abundant egg yolk protein within the oocyte, whereas mesenteria gland cells synthesize mucin 5B, which was found to be the main component of the jelly sac. These findings shed light on the sexual reproduction program in cnidarians and suggest a high conservation with proteins governing oogenesis in Bilateria.